2022
DOI: 10.1038/s41421-022-00423-0
|View full text |Cite
|
Sign up to set email alerts
|

GFAT1-linked TAB1 glutamylation sustains p38 MAPK activation and promotes lung cancer cell survival under glucose starvation

Abstract: Reprogrammed cell metabolism is deemed as one of the hallmarks of cancer. Hexosamine biosynthesis pathway (HBP) acts as an “energy sensor” in cells to regulate metabolic fluxes. Glutamine-fructose-6-phosphate amidotransferase 1 (GFAT1), the rate-limiting enzyme of HBP, is broadly found with elevated expression in human cancers though its exact and concrete role in tumorigenesis still remains unknown and needs further investigation. P38 mitogen-activated protein kinase (MAPK) is an important component of stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Notably, glutamine-fructose-6-phosphate amido transferase 1 (GFAT1), a crucial rate-limiting enzyme in the hexosamine biosynthesis pathway (HBP), was found to be overexpressed with a high expression factor. The HBP pathway constitutes a vital branch of glucose metabolism, acting as a glucose flux sensor that facilitates the regulation of metabolic processes . Earlier studies have demonstrated that during glucose deprivation, GFAT1 is upregulated and the HBP pathway is activated to ensure cellular survival. , Furthermore, the HBP pathway generates the crucial final product uridine diphosphate-N-acetylglucosamine (UDP-GlcNAc), which serves as a fundamental substrate for protein O-linked β-N-acetylglucosamine (O-GlcNAc) modification (O-GlcNAcylation).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, glutamine-fructose-6-phosphate amido transferase 1 (GFAT1), a crucial rate-limiting enzyme in the hexosamine biosynthesis pathway (HBP), was found to be overexpressed with a high expression factor. The HBP pathway constitutes a vital branch of glucose metabolism, acting as a glucose flux sensor that facilitates the regulation of metabolic processes . Earlier studies have demonstrated that during glucose deprivation, GFAT1 is upregulated and the HBP pathway is activated to ensure cellular survival. , Furthermore, the HBP pathway generates the crucial final product uridine diphosphate-N-acetylglucosamine (UDP-GlcNAc), which serves as a fundamental substrate for protein O-linked β-N-acetylglucosamine (O-GlcNAc) modification (O-GlcNAcylation).…”
Section: Resultsmentioning
confidence: 99%
“…O-GlcNAcylation is implicated in gene expression, pathogen infection, and metabolism . Moreover, under glucose-deprived conditions, the metabolic activity of GFAT1 drives glutamylation of TAB1 in a TTLL5-dependent manner, thus activating the MAPK pathway . The combined results of Raman spectroscopy and proteomics analysis demonstrate that under EVs exposure macrophages exhibit a deficiency in glucose, accompanied by a metabolic shift from glucose metabolism to lipid metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the presence of glutamine in the cell culture media controls the interaction of GFAT1 with mTORC2 in high-speed membrane-containing fractions [ 40 ]. Furthermore, GFAT1 associates with the transforming growth factor-β-activated kinase-1-binding protein 1 (TAB1) during glucose starvation [ 43 ]. The GFAT1-TAB1 interaction allows the formation of a complex with TTLL5, which is involved in the ligation of glutamate to substrates, such as TAB1.…”
Section: De Novo Hexosamine Biosynthesismentioning
confidence: 99%
“…The latter consequently enhances p38 MAPK activation and autophagy during glucose deprivation, thus increasing the survival of lung adenocarcinoma cell lines. The central role of GFAT1 in this process is underlined by its enzymatically inactive mutant, GFAT1 H577A, which is unable to rescue the growth of GFAT1-deleted cells during glucose starvation [ 43 ]. These findings suggest that GFAT1 may possess functions other than its canonical role in promoting de novo hexosamine production.…”
Section: De Novo Hexosamine Biosynthesismentioning
confidence: 99%